Effect of monochromatic light on the circadian clock of cultured chick retinal tissue. (May 2020) - Bian, Jiang; Wang, Zixu; Dong, Yulan; Cao, Jing; Chen, Yaoxing
Abstract: The central biological clock system of bird is formed by hypothalamus suprachiasmatic nucleus, pineal gland and retina thereby interacting with each other in a neuroendocrine loop. Previous results have confirmed that monochromatic light can influence the clock genes in the pineal gland, hypothalamus and retina of chicks in vivo. The present work was conducted to study whether the cultured retinal tissue of chick could maintain the circadian oscillation and whether the monochromatic light affect the expression level of cultured retinal circadian clock in vitro. Retinal tissues of 0-day-old chicks were cultured in vitro under 4 light treatments (white, red, green and blue lights) with light dark cycle 12:12 and constant dark. The tissues and culture medium were collected every each 4 h. Melanopsin, clock genes, cAanat, the positive-regulating clock proteins and melatonin were measured. The results showed that cOpn4-1, cOpn4-2, cBmal1, cCry1, cPer2, cPer3, cAanat and melatonin concentrations possessed a significant circadian rhythm in cultured chick retina tissues under different monochromatic lights; while, in constant dark, cBmal1, cCry1, cPer2, cPer3, cAanat and melatonin concentration possessed a significant circadian rhythm. Green light promoted the circadian expression level of cOpn4-1, cOpn4-2, cBmal1, cAanat and BMAL1 proteins and the circadian rhythm of melatonin secretion of retina by increasing the mesors and amplitudes. In addition, green light significantly increased the average expression levels of cClock, cBmal2 and CLOCK proteins which were expressed arrhythmically. Results suggested that the retina is a central oscillator with autonomous circadian rhythm. In isolated retina tissues, green light activated the expression of melanopsin and promoted the expression of positive-regulating clock genes, thereby up-regulating the expression of cAanat and resulting the increasing of the synthesis and secretion of melatonin. Highlights: The cultured chick retinal tissue was established, and the biological clock of retina was affected by the color of light. In constant dark, the molecular clock and melatonin in isolated chick retina tissue maintained circadian oscillation. Green light increased melatonin and  cAanat  by enhancing the circadian expression of melanopsin and positive clock genes.